El rol de la enfermera en el cuidado de las alergias respiratorias en menores de 15 años, del sector cerro del Carmen, cantón Guayaquil, enero-agosto 2014 - Macías Luna, Lucitania Jacquelines (2015)
The study of "Nurse's Role in the Care Respiratory Allergies in children under 15 years of “Cerro del Carmen”, sector Canton Guayaquil, January-August 2014" is a project that will determine the cognitive, environmental, social factors and economic factors that directly and indirectly influence on respiratory health and quality of life of children under 15 years, besides being an important source of information for those interested in making social projects. Since ancient times, the main concern of humanity has been to have stability and health welfare , ie increase and ensure life expectancies for the future , so it has been necessary to perform all kinds of research, be it scientific, medical or experimental, to help achieve these goals. In the Cerro del Carmen de Guayaquil Sector , no study to determine the state of respiratory health , the predominant type of allergy and the risk factors that are directly influencing the quality of life of children in the sector who constitute the most affected population worldwide. The main reason for this study arises from direct observation through coexistence and own professional experience related to a database of allergic patients; for which I work as a nursing assistant in a cross allergy diagnosis and prevention of allergies, created from the impending need for specialists allergists in the city of Guayaquil. In view of the need for this study was determined as main objectives : to investigate the role of the professional nurse in the care of respiratory allergy in children under 15 years and determine the socioeconomic characteristics and habits that influence the disease. The use of essential strategies for answers to the verification of the assumptions made, among these instruments have a poll concocted by the researcher, it consists of three main modules: • First it will help us understand aspects of the identification and characterization of the family socioeconomic, • Second will address issues related to family health and • Third will identify the aspects related to the individual health status of affected children. The future of humanity is characterized by a constant evolution and development in all areas, this phenomenon leads to concerns about the longevity and the continuation of the human race. The worry today's health and welfare of the population of children allergic ensures continuity of future generations. In conclusion, decreased morbidity and mortality rates and improve the quality of life of the allergic child population is a challenge that the scientific community will continue to seek to achieve, however, this would be impossible if the people involved; patients, parents and nurses do not contribute effectively and voluntarily take actions aimed at preserving the welfare of our own health and our environment.